Blood Lactate Level as Predictor of Early Outcome after Cardiac Surgery under Cardiopulmonary Bypass - Azad, Md Abul Kalam; Quashem, Md Abul; Karim, Md Rezaul; Hasan, Md Kamrul (University Heart Journal, 2018)
We examined the hypothesis that high blood lactate level in ICU patient after adult cardiac surgery under cardiopulmonary bypass is associated with early adverse outcome. The objective of this study was to evaluate whether blood lactate level after cardiac surgery is predictor of the early outcome after adult cardiac surgery under CPB. In this prospective observational study total 100 patients were enrolled who underwent elective cardiac surgery under CPB as per inclusion and exclusion criteria. Blood lactate levels > 3mmol/ L 6 hours after ICU transfer were present in 57(57%) patients. The binary logistic regression analysis showed that blood lactate level 6 hours after ICU transfer is an independent predictor for prolonged mechanical ventilation time (OR 2.417, 95% CI 1.272 - 4.596, p = .007), prolonged ICU stay (OR 1.562, 95% CI 1.181 - 2.067, p = .002), neurological deficit (OR 2.432, 95% CI 1.539 - 3.843, p = .001), pulmonary complication (OR 1.301, 95% CI 1.011 - 1.676, p = .041), arrhythmia (OR 1.444, 95% CI 1.102 - 1.893, p = .008), renal dysfunction (OR 1.838, 95% CI 1.352 - 2.497, p = .001) and mortality (OR 1.822, 95% CI 1.123- 2.955, p = .015). In conclusion, blood lactate level 6 hours after ICU transfer is an independent risk factor for worse outcomes in adult patients including mortality after cardiac surgery under CPB. University Heart Journal Vol. 13, No. 2, July 2017; 50-54